A Review of Aerospike Nozzles: Current Trends in Aerospace Applications - Isaac Ramirez Cardenas; Santiago Laín; Omar Dario Lopez (Aerospace, 2025)
The aerospike nozzle has emerged as a revolutionary technology in rocket propulsion, overcoming the limitations of conventional nozzles by dynamically adjusting the expansion of exhaust gases according to ambient pressure. This results in greater efficiency and fuel savings. Thanks to advancements in materials, computational simulations, and additive manufacturing, aerospike nozzle design has surpassed historical barriers, not only enhancing the performance of multi-stage engines but also enabling the development of new space vehicles such as single-stage-to-orbit (SSTO) systems. These promise a simpler, reusable, and more cost-effective launch architecture. In summary, aerospike technology inspires a new era in space exploration, transforming propulsion efficiency and paving the way for more accessible and sustainable future space transportation systems.